Investigate the concept of justification in the product (Nallay Daroon) of Shekh Mohammady Khall (A viewpoint of Analayze the critical discourse) - Salih, Asst. L. Sarwar Sadulla (Sulaimani Journal for Humanities, 2023)
Shekh Mohammady Khall is one of the prominent characters and an intellectual of Kurd. In his time, he was an innovative imam and sorrows and significant issues of his nation were prior of his work. The writer in the product (Nallay Daroon) which are some essays were written in the specific circumstance, that justify the reader’s trust. So, he wanted to compose a high discourse and believer that reader trust it in order to not collapse and scroam. Hereby, the discourses of Shekh Mohammady Khall in different manner to get trust or justification. The result shows that persist of the writer is in the way of language ang goring back and indicate the verses of the holy Quran, hadith, tradition, the texts of the poems, characters, and proverbs, he wanted to produce the high discourses such as religious, humanity, literary, philosophy, social, nationality and culture. All of the discourses are builder and built, it means the discourses are practical socially that they build social situation and also, they built the other social practical aspects.
Keywords: The concept of discourse; the theory of critical discourse analysis; the concept of justification; the lament of the mind